The given partial differential equation is
"(D^3-DD'^2+D^2+DD')z=(x+2)+e^{x-y}"This is non homogeneous linear partial differential equation with constant coefficients .The solution of the given PDE is obtained by finding C.F and P.I
Thus ,solution = C.F + P.I
Calculating C.F
"D^3-DD'^2+D^2+DD'=0\\\\or, D(D^2-D'^2+D+D')=0\\\\or, D\\{(D+D')(D-D')+(D+D')\\}=0\\\\or, D(D+D')(D-D'+1)=0"
Now comparing with "(D-m_1D'-c_1)(D-m_2D'-c_2)(D-m_3D'-c_3)z=0,we \\space get"
"Rewriting \\space D(D+D')(D-D'+1)=0 \\space as\\\\(D-0*D'-0)(D-(-1)*D'-0)(D-1*D'+1)=0"
"\\therefore m_1=0,m_2=-1,m_3=1\\\\and \\space c_1=0,c_2=0,c_3=1"
"\\therefore C.F = e^{0*x}f_1(y+0*x)+ e^{0*x}f_2(y-x)+e^{1*x}f_3(y+x)\\\\or, C.F = f_1(y+0*x)+ f_2(y-x)+e^{x}f_3(y+x)\\\\C.F = e^{0*x}f_1(y+0*x)+ e^{0*x}f_2(y-x)+e^{1*x}f_3(y+x)\\\\or, C.F = f_1(y)+ f_2(y-x)+e^{x}f_3(y+x)"
Calculating P.I
"P.I = \\frac{1}{f(D,D')}\\{e^{x-y}+x+2\\}\\\\or, P.I = \\frac{1}{f(D,D')}e^{x-y}+\\frac{1}{f(D,D')}(x+2)\\\\or,P.I = (P.I)_1+(P.I)_2"
"Now, (P.I)_1 = \\frac{1}{f(D,D')}e^{x-y}\\\\"
"= \\frac{1}{D^3-DD'^2+D^2+DD'}e^{x-y}"
Now replacing D by 1 and D' by (-1) we get "D^3-DD'^2+D^2+DD' = 0," so following the working rule
"(P.I)_1 = \\frac{x}{\\frac{\\delta}{\\delta D}D^3-DD'^2+D^2+DD'} e^{x-y}\\\\"
"= \\frac{x}{3D^2-D'^2+2D+D'} e^{x-y}"
"= \\frac{x}{3-1+2-1} e^{x-y}"
"=\\frac{x}{3}e^{x-y}"
"(P.I)_1 = \\frac{x}{3}e^{x-y}."
"Now, (P.I)_2 = \\frac{1}{f(D,D')}(x+2)"
"= \\frac{1}{ D(D+D')(D-D'+1)} (x+2)"
"=\\frac{1}{D(D+D')}\\{1+(D-D')\\}^{-1} \\space (x+2)"
"=\\frac{1}{D(D+D')}(1+(D-D')+(D-D')^2......) \\space (x+2)"
"= x +2+1"
"=x+3" "\\because D(x)=1 \\space D'(1)=0"
"(P.I)_2 = x+3"
"\\therefore solution \\space = C.F+P.I\\\\"
"= f_1(y)+ f_2(y-x)+e^{x}f_3(y+x) \\space + \\frac{x}{3}e^{x-y} + (x+3)"
ANSWER
Comments
Leave a comment